Crystal morphologies on a cordierite glass surface - Ziemath, E. C. [UNESP]; Diaz-Mora, N.; Zanotto, E. D. (My University, 1997)
With suitable thermal treatments, a nearly stoichiometric cordierite glass (2 MgO.2 Al2O3. 5 SiO2) shows a variety of crystal morphologies on the external surfaces: lozenges, regular and elongated hexagons, spherical and square shaped particles. We initially identified these morphologies through optical and scanning electron microscopy techniques. Their structural features were distinguished by x-ray diffraction patterns, infrared and Roman microprobe spectra. We concluded that there are close structural similarities for: lozenges and glass matrix; regular and elongated hexagons; spherical and square particles. The ordering degree increases in the following sequence: glass matrix, lozenges, hexagons, squares and spheres. The lozenge crystals are known as X-phase. The hexagons belong to the μ-cordierite (high quartz solid solution) metastable phase and the squares and spheres to the α-cordierite stable phase.